1981
DOI: 10.1097/00004032-198107000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Inhaled 241Am Oxide Particles of Various Sizes from Beagle Dogs Using Lung Lavage and Chelation Treatment

Abstract: The combined treatments of lung lavage and chelation therapy were evaluated for the removal of inhaled 24'Am02. Twenty-four Beagle dogs were divided into four equal groups; three groups were exposed to aerosols of diff erent-sized monodisperse particles of ='Am02; Group 1, 0.75 pm aerodynamic diameter (AD) particles; Group 2, 1.5 pm AD particles and Group 3,3.0 pm AD particles; and the fourth group was exposed to an aerosol of polydisperse particles of "'Am02 with an activity median aerodynamic diameter (AMAD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies in a canine (beagle) model have demonstrated that the use of bronchoalveolar lavage (BAL) will facilitate the removal of inhaled 144 Ce, resulting in greatly increased survival times in treated animals when compared to animals not subjected to BAL (105). BAL also removed about 50% of inhaled 241 Am particles and similarly improved survival in dogs (106). Currently, therefore, BAL is the only treatment available to clear nonsoluble radioactive particle in the lung, and has been used following incidents of internal contamination (107); however, it is an invasive procedure.…”
Section: Workhop Reportmentioning
confidence: 99%
“…Studies in a canine (beagle) model have demonstrated that the use of bronchoalveolar lavage (BAL) will facilitate the removal of inhaled 144 Ce, resulting in greatly increased survival times in treated animals when compared to animals not subjected to BAL (105). BAL also removed about 50% of inhaled 241 Am particles and similarly improved survival in dogs (106). Currently, therefore, BAL is the only treatment available to clear nonsoluble radioactive particle in the lung, and has been used following incidents of internal contamination (107); however, it is an invasive procedure.…”
Section: Workhop Reportmentioning
confidence: 99%